Genetic divergence among peach palm progenies for palm heart characters - Negreiros, Jacson Rondinelli da Silva; Bergo, Celso Luis; Miqueloni, Daniela Popim; Lunz, Aureny Maria Pereira (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to estimate the genetic diversity of peach palm progenies, based on palm heart agronomic traits. A randomized block design was used in 10x10 triple lattice, with 100 treatments (progenies) and three replicates. The following evaluations were made: palm heart base mass, first-rate and second-rate palm heart productivity, number of plants per plot, and palm heart diameter. The genetic divergence was estimated by generalized Mahalanobis distance, as a dissimilarity measure, and by the Tocher optimization method and canonical variables, for group formation. The progenies formed 26 groups. Cumulative variance of the first three canonical variables was 75.12%. Plant per plot and second-rate palm heart mass, indirectly related to the first-rate palm heart mass, were the most important characters in the discrimination of progenies, in the first canonical variable (35.77%). Mass of the palm heart base was indirectly related to the second-rate palm heart productivity and number of plants per plot, in the second canonical variable (22.93%), and to the first-rate palm heart productivity in the third canonical variable (16.42%). Seventeen progenies of four divergent groups (G3, G5, G11 and G12) have potential for selection as to palm heart yield in the breeding program of peach palm.